Conceptual modelling tool for novice designers. (9th December 2008) - Kop, Christian
Using UML class diagrams or OWL specifications, the designer is always confronted with the same problem: which concept should be modelled as a class and which concept can be pruned to an attribute (DatatypeProperty)? In this paper, a very simple and easy methodology to derive classes and attributes from a network of concepts will be introduced. Using this methodology, the designer will be even able to start modelling with controlled English language patterns. At the end, a prototype implementation will show how they all fit together.